Mode 1 Fracture Toughness Of Palm And Coir Fibre Reinforced Composite Via Double Cantilever Beam Test - Balakrishnan, Sakthisivan (Universiti Sains Malaysia, 2021)
This is a study of the double vacuum bagging (DVB) method employment in the fabrication process of the composite laminate by using natural fibres such as palm and coir fibre. In this world and upcoming world, natural fibres have become the alternative choices of the reinforcement material due to its eco-friendly towards the environment, biodegradability, low density, low cost etc. The purpose of this study is to initiate the application of double vacuum bagging method (DVB) in fabricating the natural fibre reinforced composite. Not only that, fabrication process which able to produce composite material with a higher quality in terms of better surface finishing and mechanical properties is developed in this study. Natural fibres such as palm and coir fibre are used as the reinforcement material in the fabrication process whereas the matrix, EpoxAmite 103 is chosen. Every composite laminate, a minimum of two plies are rolled until the total thickness of a minimum of 3 mm is obtained, then the fibre plies are weighed to calculate the mass of the resin according to the volume fraction. The measured resin is then applied to the fibre plies by the method of wet hand layup. After that, the double vacuum bagging (DVB) method are implanted to the fibre for further compression. At least 5 specimens are cut and loading blocks are attached at the end of the initiation site of the specimen which is required for the double cantilever beam (DCB) test according to the standard of ASTM D5528. As for the ASTM D5045, the number of fibre plies depend on the thickness of the specimen required based on the calculations. Hence, the composite laminate is then cut into the length and width that is required for the compact tension (CT) test according to the ASTM D5045 which will obtain from the calculation as well. A sharp tip crack length is created by using a fresh razor blade. Besides that, this study showed the importance of the vacuum bagging plays a huge important role in the fabrication process where a slight bagging leakage will affect the mechanical properties of the specimens. Not only that, the uniform vacuum pressure and pressure distribution are important as well as it produces composite laminate with a high quality. The double bagging method used in the study is capable in producing composites with a higher Young’s Modulus compared to other method of fabrication process such as resin infusion and wet hand layup. However, the DCB test results were invalid as, it only applicable to unidirectional fibre reinforced specimen while the CT test the energy release rate for the coconut fibre reinforced composite is higher compared to previous study. Further research is required to improve the double vacuum bagging (DVB) method during the fabrication process.